2003
DOI: 10.1093/hmg/ddg159
|View full text |Cite
|
Sign up to set email alerts
|

The p38 subunit of the aminoacyl-tRNA synthetase complex is a Parkin substrate: linking protein biosynthesis and neurodegeneration

Abstract: Parkinson's disease (PD) is a severe neurological disorder, characterized by the progressive degeneration of the dopaminergic nigrostriatal pathway and the presence of Lewy bodies (LBs). The discovery of genes responsible for familial forms of the disease has provided insights into its pathogenesis. Mutations in the parkin gene, which encodes an E3 ubiquitin-protein ligase involved in the ubiquitylation and proteasomal degradation of specific protein substrates, have been found in nearly 50% of patients with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
142
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(146 citation statements)
references
References 59 publications
3
142
1
Order By: Relevance
“…Next, the effects of c-Abl on parkin ubiquitination of AIMP2 were monitored. Parkin ubiquitinates AIMP2 as previously described (8,20) and Y143F parkin also ubiquitinates AIMP2 (Fig. 3C).…”
Section: Resultssupporting
confidence: 79%
“…Next, the effects of c-Abl on parkin ubiquitination of AIMP2 were monitored. Parkin ubiquitinates AIMP2 as previously described (8,20) and Y143F parkin also ubiquitinates AIMP2 (Fig. 3C).…”
Section: Resultssupporting
confidence: 79%
“…S-nitrosylation of parkin inhibits its ubiquitination and protective function (Chung et al, 2004;Yao et al, 2004); thus, accumulation of parkin substrates may also contribute to the neurodegeneration in sporadic PD. A number of parkin substrates have been identified including, CDCrel-1, CDCrel-2, synphilin-1, glycosylated ␣-synuclein, ␤-tubulin, cyclin E, synaptotamin XI (SytXI), parkin-associated endothelin-like receptor (Pael-R), and p38/JTV-1 subunit of the multi-tRNA synthetase complex (Zhang et al, 2000;Chung et al, 2001;Imai et al, 2001;Shimura et al, 2001;Choi et al, 2003;Corti et al, 2003;Huynh et al, 2003;Ren et al, 2003;Staropoli et al, 2003;Jiang et al, 2004). CDCrel-1, CDCrel-2, Pael-R, and cyclin E appear to be upregulated in AR-JP brains (Imai et al, 2001;Choi et al, 2003;Staropoli et al, 2003), but none of these substrates have been reported to be upregulated in parkin knockout (KO) mice.…”
Section: Introductionmentioning
confidence: 99%
“…The ensuing accumulation of parkin substrates is believed, in turn, to induce the cellular toxicity and dopamine neuron loss seen in PD. Although numerous parkin substrates have been identified (Zhang et al, 2000;Chung et al, 2001;Imai et al, 2001;Corti et al, 2003;Staropoli et al, 2003), there is still controversy as to which of these accumulate in the brains of parkin knockout (KO) mice (Goldberg et al, 2003;Itier et al, 2003;Von Coelln et al, 2004;Ko et al, 2005;Perez and Palmiter, 2005;Periquet et al, 2005) and as to their respective roles in the pathogenesis of PD (Cookson, 2005;Moore et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The ensuing accumulation of parkin substrates is believed, in turn, to induce the cellular toxicity and dopamine neuron loss seen in PD. Although numerous parkin substrates have been identified (Zhang et al, 2000;Chung et al, 2001;Imai et al, 2001;Corti et al, 2003;Staropoli et al, 2003), there is still controversy as to which of these accumulate in the brains of parkin knockout (KO) mice (Goldberg et al, 2003;Itier et al, 2003;Von Coelln et al, 2004;Ko et al, 2005;Perez and Palmiter, 2005;Periquet et al, 2005) and as to their respective roles in the pathogenesis of PD (Cookson, 2005;Moore et al, 2005).In addition to its traditional role, Ub can serve as a reversible posttranslational modification that regulates the function of tagged proteins without necessarily leading to their destruction by the proteasome (Hicke and Dunn, 2003;Mukhopadhyay and Riezman, 2007). Depending on the length and architecture of the Ub chain, ubiquitination has been implicated in a variety of cellular functions as diverse as signal transduction, transcription, and membrane trafficking (Mukhopadhyay and Riezman, 2007).…”
mentioning
confidence: 99%